Deficiency of interleukin-19 exacerbates lipopolysaccharide/D-galactosamine-induced acute liver failure - FUJIMOTO, Yasuyuki (J Vet Med Sci, 2020)
Interleukin (IL)-19 is a cytokine clustered in the IL-20 cytokine superfamily with both anti-inflammatory and pro-inflammatory aspects depending on the etiology of inflammatory disease. The function of IL-19 has been evaluated in cutaneous and inflammatory bowel diseases, but has not been studied in liver diseases. Here, we examined the effect of IL-19 on acute liver failure (ALF) using two mouse models of ALF: lipopolysaccharide and D-galactosamine (LPS/GalN)-induced model and concanavalin A (ConA)-induced model. In the LPS/GalN-induced ALF model, which is mainly caused by the innate immune response of liver macrophages, IL-19 knockout (KO) mice showed increased plasma level of liver deviation enzymes, aspartate aminotransferase (AST) and alanine aminotransferase (ALT) compared with wild-type (WT) mice. In histopathology of liver sections, IL-19 KO mice exacerbated liver injury with marked hemorrhagic lesions and hepatocellular death in the liver compared with WT mice. In this model, mRNA expressions of pro-inflammatory chemokines, CCL2 and CCL5 were increased in liver tissue from IL-19 KO mice compared with WT mice. Moreover, the mRNA expressions of IL-19 and its receptor subunit were induced in liver tissue by LPS/GalN administration. However, there is no difference in liver injury between WT and IL-19KO in the ConA-induced ALF model induced by CD4(+) T cell activation. These data suggest that IL-19 has a protective effect against inflammation-mediated liver injury, which is dependent on the etiology.